2012
DOI: 10.1371/journal.pone.0050689
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Interaction of CheD with CheC and the Chemoreceptors Compared to Its Enzymatic Activity during Chemotaxis in Bacillus subtilis

Abstract: Bacillus subtilis use three systems for adaptation during chemotaxis. One of these systems involves two interacting proteins, CheC and CheD. CheD binds to the receptors and increases their ability to activate the CheA kinase. CheD also binds CheC, and the strength of this interaction is increased by phosphorylated CheY. CheC is believed to control the binding of CheD to the receptors in response to the levels of phosphorylated CheY. In addition to their role in adaptation, CheC and CheD also have separate enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…Fractions containing the purified proteins were identified with SDS-PAGE. The fractions containing the purified protein were pooled and refolded by dialyzing three times against TKMD-G (50 mM Tris-Cl, pH 8.0, 5 mM MgCl 2 , 50 mM KCl, 0.1 mM dithiothreitol, 10% glycerol, pH 8.0) at 4°C for 2 h, followed by an overnight charge at 4°C (39). Gel filtration was employed to further purify the refolded lyases using a 16-mm-diameter HiPrep Sephacryl S-200 HR (GE Healthcare) gel filtration column charged with TKMD-G. Fractions were collected using TKMD-G at 0.5 ml per min to elute the purified protein.…”
Section: Methodsmentioning
confidence: 99%
“…Fractions containing the purified proteins were identified with SDS-PAGE. The fractions containing the purified protein were pooled and refolded by dialyzing three times against TKMD-G (50 mM Tris-Cl, pH 8.0, 5 mM MgCl 2 , 50 mM KCl, 0.1 mM dithiothreitol, 10% glycerol, pH 8.0) at 4°C for 2 h, followed by an overnight charge at 4°C (39). Gel filtration was employed to further purify the refolded lyases using a 16-mm-diameter HiPrep Sephacryl S-200 HR (GE Healthcare) gel filtration column charged with TKMD-G. Fractions were collected using TKMD-G at 0.5 ml per min to elute the purified protein.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies revealed that CheD also participates with CheC and CheYp in a negative feedback loop, which controls the amount of CheD free to bind and activate the receptors in response to CheYp (Chao et al, 2006;Muff and Ordal, 2007). The two roles are distinct: of the two, the feedback loop is thought to be more important for chemotaxis Yuan et al, 2012). Indeed, replacing the target glutamines with glutamates does not remove the requirement of CheD for optimal chemotaxis.…”
Section: Chedmentioning
confidence: 99%
“…CheC is a weak CheYp phosphatase and CheD is a receptor deamidase (Kristich and Ordal, 2002). However, the enzymatic functions of these two proteins are secondary to their role as adaptation proteins (Muff and Ordal, 2007;Glekas et al, 2012;Yuan et al, 2012). In particular, these two proteins participate in a negative feedback loop that regulates CheA activity in response to CheYp levels (Muff and Ordal, 2007;Glekas et al, 2012;Yuan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, B. burgdorferi has a putative gene encoding CheD, which is not found in E. coli (5). CheD is relatively well characterized in Bacillus subtilis and Thermotoga maritima (27)(28)(29)(30). In B. subtilis, CheD plays an important role in motility and chemotaxis.…”
mentioning
confidence: 99%